Shopping Detail Information and Home Freezer Sampling Confirmed the Role of Commercial, Modified-Atmosphere Packaged Meatballs as a Vehicle for Listeriosis in Finland - Keto-Timonen, Riikka; Markkula, Annukka; Halkilahti, Jani; Huttunen, Reetta; Räsänen, Sirpa; Salmenlinna, Saara; Heikkilä, Anne; Puisto, Mia; Närhinen, Maria; Hakkinen, Marjaana; Korkeala, Hannu; Jalava, Katri (Frontiers in Public Health, 2019)
In November 2016, an elderly patient was diagnosed with Listeria monocytogenes bacteremia in Finland. Grocery store loyalty card records and microbiological investigation of foods found in the home fridge and freezer of the patient revealed commercial, modified-atmosphere packaged meatballs as the source of the infection. Investigation of the meatball production plant revealed that the floor drain samples were contaminated with the same L. monocytogenes strain as those isolated from the patient and meatballs. Ready-to-eat meatballs were likely contaminated after heat treatment from the production environment before packaging. Long-term cold storage, modified-atmosphere conditions, and the absence of competing bacteria presumably enhanced the growth of L. monocytogenes. We recommend that collection of shopping details and home fridge and freezer sampling should be part of surveillance of all cases of L. monocytogenes infections to complement information obtained from in-depth interviews.